Improved methods of carnivore faecal sample preservation, DNA extraction and quantification for accurate genotyping of wild tigers. - Patlolla Anuradha Reddy (PLoS ONE, 2012)
Background Non-invasively collected samples allow a variety of genetic studies on endangered and elusive species. However due to low amplification success and high genotyping error rates fewer samples can be identified up to the individual level. Number of PCRs needed to obtain reliable genotypes also noticeably increase. Methods We developed a quantitative PCR assay to measure and grade amplifiable nuclear DNA in feline faecal extracts. We determined DNA degradation in experimentally aged faecal samples and tested a suite of pre-PCR protocols to considerably improve DNA retrieval. Results Average DNA concentrations of Grade I, II and III extracts were 982pg/µl, 9.5pg/µl and 0.4pg/µl respectively. Nearly 10% of extracts had no amplifiable DNA. Microsatellite PCR success and allelic dropout rates were 92% and 1.5% in Grade I, 79% and 5% in Grade II, and 54% and 16% in Grade III respectively. Our results on experimentally aged faecal samples showed that ageing has a significant effect on quantity and quality of amplifiable DNA (p<0.001). Maximum DNA degradation occurs within 3 days of exposure to direct sunlight. DNA concentrations of Day 1 samples stored by ethanol and silica methods for a month varied significantly from fresh Day 1 extracts (p<0.1 and p<0.001). This difference was not significant when samples were preserved by two-step method (p>0.05). DNA concentrations of fresh tiger and leopard faecal extracts without addition of carrier RNA were 816.5pg/µl (±115.5) and 690.1pg/µl (±207.1), while concentrations with addition of carrier RNA were 49414.5pg/µl (±9370.6) and 20982.7pg/µl (±6835.8) respectively. Conclusions Our results indicate that carnivore faecal samples should be collected as freshly as possible, are better preserved by two-step method and should be extracted with addition of carrier RNA. We recommend quantification of template DNA as this facilitates several downstream protocols.